DATA-DRIVEN HR: MEASURING THE IMPACT OF ANALYTICS ON EMPLOYEE PERFORMANCE - Sindhuja A; Dunstan Rajkumar A (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
With the advent of globalization, there has been a significant transformation in the area of human resource management. This necessitates organizations promoting a competent workforce to gain a competitive advantage in the industrial world. Despite the evolution in human resource management, companies are yet to realize their full potential due to resistance from employees. The study, therefore, underscores the importance of integrating HR analytics into performance management systems, emphasizing its role in driving data-driven decision-making, fostering fairness in appraisals, and supporting strategic workforce management. This study, therefore, explores the impact of HR analytics on employee performance from the perspectives of HR managers and professionals, focusing on five core performance indicators: Work Efficiency (WE), Employee Productivity (EP), Project Completion Rates (PCR), Quality of Work (QW), and Employee Team Collaboration (ETC). Utilizing survey responses from 150 HR professionals across various industries, the research employs correlation and regression analyses to assess the relationship between HR analytics and employee performance outcomes. The study uses structural equation modeling to examine the mediating relationship between human resource analytics, motivation, and employee performance. The findings reveal a strong positive correlation between HR analytics and enhanced employee performance metrics. HR analytics have a positive influence on performance management, talent acquisition, employee engagement, and team collaboration while also contributing to timely project completion and overall productivity improvements. Furthermore, the results suggest that organizations leveraging HR analytics are better positioned to enhance employee performance and optimize HR activities, with the moderating effects of variables such as years of HR experience and company size playing significant roles. JEL Classification Codes: O15, M12, J24.